Optimal body balance disturbance tolerance skills as a methodological basis for selection of firefighters to solve difficult rescue tasks - Władysław Jagiełło; Zbigniew Wójcicki; Bartłomiej J Barczyński; Artur Litwiniuk; Roman Maciej Kalina (Annals of Agricultural and Environmental Medicine, 2014)
The aim of this study is the methodology of optimal choice of firefighters to solve difficult rescue tasks. 27 firefighters were analyzed: aged from 22–50 years of age, and with 2–27 years of work experience. Body balance disturbance tolerance skills (BBDTS) measured by the ‘Rotational Test’ (RT) and time of transition (back and forth) on a 4 meter beam located 3 meters above the ground, was the criterion for simulation of a rescue task (SRT). RT and SRT were carried out first in a sports tracksuit and then in protective clothing. A total of 4 results of the RT and SRT is the substantive base of the 4 rankings. The correlation of the RT and SRT results with 3 criteria for estimating BBDTS and 2 categories ranged from 0.478 (p<0.01) – 0.884 (p<0.01) and the results of SRT 0.911 (p<0.01). The basic ranking very highly correlated indicators of SRT (0.860 and 0.844), while the 6 indicators of RT only 2 (0.396 and 0.381; p<0.05). There was no correlation between the results of the RT and SRT, but there was an important partial correlation of these variables, but only then was the effect stabilized. The Rotational Test is a simple and easy to use tool for measuring body balance disturbance tolerance skills. However, the BBDTS typology is an accurate criteria for forecasting on this basis, including the results of accurate motor simulations, and the periodic ability of firefighters to solve the most difficult rescue tasks.